Assessment of management of a golf course by means of sustainability indicators - Pacini, Gaio Cesare; Staglianò, Nicolina; Meo, Francesco; Lazzerini, Giulio; Vazzana, Concetta; Argenti, Giovanni (Italian Journal of Agronomy, 2016)
Golf courses are supposed to produce remarkable negative effects on the environment, due to some techniques involved in their management. To provide data useful for the proper assessment of the agro-environmental sustainability of a golf course, the framework agro-environmental sustainability information system (AESIS) was used, utilizing a set of indicators suitable to evaluate different dimensions of sustainability (physical, ecological, productive and social). The management of areal golf course located in Tuscany (central Italy) was compared to an alternative land use of the same area represented by an ordinary farm based on a sunflower-wheat rotation. Assessment indicators were selected by applying a conceptual model based on ecology theory and were calculated considering site-specific production and pedo-climatic features of the area. Different weighting scenarios were hypothesized in order to have different management options assessed and to carry out a targeted sensitivity analysis. Main results confirmed the significant impact of golf management on some ecological characteristics but the holistic assessment of AESIS approach permitted an overall evaluation that comprised a wide range of different issues. AESIS demonstrated to be a practical and adaptive tool able to perform an efficient comparison of possible land destinations.